Code-mixing Used By Putri Tanjung To People Who Had Different Statuses In Ngrobrol Sore Semaunya Podcast - Katsujai Jathniel Ciputra; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study was conducted to investigate the code-mixing types used by Putri Tanjung when she was talking to Hedi Rusdian, a non-government official who had the same status as her, and when she was talking to Erick Thohir, a government official who had a higher status than her with its differences and similarities. In this study, the theory of code-mixing types by Muysken (2000) and the status scale theory by Holmes (2013) were used. A qualitative approach was employed in this study. The findings revealed that Putri Tanjung chose a different type of code-mixing when talking to people with different statuses. This can probably happen due to the status of the interlocutors, the situation of the podcast, or the absence of appropriate terms. More studies involving podcasts are recommended. Other social factors or dimensions on code-mixing can also be included in further studies.